A Material Ecocritical Elucidation of Augusta Webster’s “Medea In Athens”, “In an Almshouse”, and “A Dilettante” - Dilek Bulut Sarıkaya (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
In addition to her being an avid campaigner of women’s suffrage and education rights, Augusta Webster (1837-1894) is a profoundly important 19th century Victorian female poet who recurrently hearkens to the necessity of obliterating boundaries, dualities, and hierarchical divisions between humans and the physical universe. Diverging from Victorian industrial society’s general propensity of perceiving nature as an inanimate commodity material to be used and abused, Webster, in her poems, captures a biological and a material understanding of the universe in which every natural entity is embedded with actively dynamic agency and vitality. Within this incessantly vibrant universe, humans’ deepest situatedness and innate connectedness to the rest of nature are repeatedly underscored in Webster’s poetry, which shows a sharp contrast to the anthropocentric assumptions of her epoch about humans’ being disparately privileged species on earth. In this regard, the main goal of this study is to analyze Augusta Webster’s “Medea in Athens”, “In an Almshouse”, and “A Dilettante” from the perspective of a recently emerging critical theory of material ecocriticism to reveal Webster’s uniquely significant ecological consciousness about the vital materiality of the universe. These poems are particularly significant in their painstaking effort to unfold the material consanguinity between human-nonhuman beings.